Diffusion Tensor Imaging Evaluation of Corticospinal Tract Hyperintensity in Upper Motor Neuron-Predominant ALS Patients - Venkateswaran Rajagopalan; Didier Allexandre; Guang H. Yue; Erik P. Pioro (Journal of Aging Research)
Amyotrophic lateral sclerosis (ALS) patients with predominant upper motor neuron (UMN) signs occasionally have hyperintensity of corticospinal tract (CST) on T2- and proton-density-(PD-) weighted brain images. Diffusion tensor imaging (DTI) was used to assess whether diffusion parameters along intracranial CST differ in presence or absence of hyperintensity and correspond to UMN dysfunction. DTI brain scans were acquired in 47 UMN-predominant ALS patients with (n=21) or without (n=26) CST hyperintensity and in 10 control subjects. Fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD) were measured in four regions of interests (ROIs) along CST. Abnormalities (P<0.05) were observed in FA, AD, or RD in CST primarily at internal capsule (IC) level in ALS patients, especially those with CST hyperintensity. Clinical measures corresponded well with DTI changes at IC level. The IC abnormalities suggest a prominent axonopathy in UMN-predominant ALS and that tissue changes underlying CST hyperintensity have specific DTI changes, suggestive of unique axonal pathology.